The PapB/FocB family protein TosR acts as a positive regulator of flagellar expression and is required for optimal virulence of uropathogenic Escherichia coli - Hirakawa, Hidetada; Shimokawa, Mizuki; Noguchi, Koshi; Tago, Minori; Matsuda, Hiroshi; Takita, Ayako; Suzue, Kazutomo; Tajima, Hirotaka; Kawagishi, Ikuro; Tomita, Haruyoshi (Frontiers in Microbiology, 2023)
Uropathogenic Escherichia coli (UPEC) is a major causative agent of urinary tract infections. The bacteria internalize into the uroepithelial cells, where aggregate and form microcolonies. UPEC fimbriae and flagella are important for the formation of microcolonies in uroepithelial cells. PapB/FocB family proteins are small DNA-binding transcriptional regulators consisting of approximately 100 amino acids that have been reported to regulate the expression of various fimbriae, including P, F1C, and type 1 fimbriae, and adhesins. In this study, we show that TosR, a member of the PapB/FocB family is the activator of flagellar expression. The tosR mutant had similar expression levels of type 1, P and F1C fimbriae as the parent strain, but flagellar production was markedly lower than in the parent strain. Flagellin is a major component of flagella. The gene encoding flagellin, fliC, is transcriptionally activated by the sigma factor FliA. The fliA expression is induced by the flagellar master regulator FlhDC. The flhD and flhC genes form an operon. The promoter activity of fliC, fliA and flhD in the tosR mutant was significantly lower than in the parent strain. The purified recombinant TosR does not bind to fliC and fliA but to the upstream region of the flhD gene. TosR is known to bind to an AT-rich DNA sequence consisting of 29 nucleotides. The characteristic AT-rich sequence exists 550-578 bases upstream of the flhD gene. The DNA fragment lacking this sequence did not bind TosR. Furthermore, loss of the tosR gene reduced motility and the aggregation ability of UPEC in urothelial cells. These results indicate that TosR is a transcriptional activator that increases expression of the flhDC operon genes, contributing to flagellar expression and optimal virulence.